Tramas para reencantar o mundo : arte, educação e culturas plots to re-enchant the world - Aguiar, Sica Martins (2017)
This paper aims to share experiences about the first seminar TRAMAS PARA REENCANTAR O MUNDO, produced by Visual Art teachers of the Colégio Pedro II Cultural Space in the year 2014. The event proposed to create a network of dialogue on art as a place of enchantment and well-being in contemporary education without knowledge of hierarchy, from moments of vivenciamento and aesthetic enjoyment